EVALUASI KINERJA PRASARANA FISIK DAERAH IRIGASI WADUK PONDOK KABUPATEN NGAWI PROVINSI JAWA TIMUR - Dani Wahyu Nugroho; Erni Mulyandari; Sumina Sumina (Journal of Civil Engineering and Infrastructure Technology, 2023)
Pondok Reservoir is one of the small reservoirs in the Bengawan Solo River Basin (DAS) which has an area of 3,450 ha and can hold as much as 29 million m3 of water. Over time, weir operation activities must be in line with weir maintenance activities. In this regard, it is necessary to evaluate the performance of irrigation areas. The method used in this study was observation and direct observation in the field by tracing the irrigation network of the D.I Pondok Reservoir and conducting secondary data analysis. The results of this study indicate that the total number of physical infrastructure assets is 139 consisting of 62 control buildings and 87 auxiliary buildings. The condition of the physical infrastructure of the Pondok D.I Reservoir for the carrier channel is 70.6% in good condition and 29.4% in a slightly damaged state, for regulatory buildings 70% is in good condition, 8.3% is in a slightly damaged condition, and 21.7% is in good condition. severely damaged condition, for supporting buildings 69.6% in good condition, 19% in slightly damaged condition, and 11.4% in severely damaged condition, for drainage and buildings in good condition, and for access/inspection roads 94% in good condition well and the remaining 6% is in slightly damaged condition. Physical infrastructure performance in the Pondok D.I Reservoir was obtained at 68.84% of 100%, meaning that this performance is included in the less criteria and needs attention